2017
DOI: 10.1371/journal.pone.0180762
|View full text |Cite
|
Sign up to set email alerts
|

Safety and pharmacodynamics of dalazatide, a Kv1.3 channel inhibitor, in the treatment of plaque psoriasis: A randomized phase 1b trial

Abstract: BackgroundDalazatide is a specific inhibitor of the Kv1.3 potassium channel. The expression and function of Kv1.3 channels are required for the function of chronically activated memory T cells, which have been shown to be key mediators of autoimmune diseases, including psoriasis.ObjectiveThe primary objective was to evaluate the safety of repeat doses of dalazatide in adult patients with mild-to-moderate plaque psoriasis. Secondary objectives were to evaluate clinical proof of concept and the effects of dalaza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 47 publications
2
119
0
1
Order By: Relevance
“…Toxicity studies with PAP‐1 and the peptidic K V 1.3 blocker ShK‐186 have so far not revealed any toxicity despite 6 months or 28 days of continuous administration in rats or rhesus macaques 4, 8. PAP‐1 has further completed IND‐enabling toxicity studies, while ShK‐186 has passed both IND toxicity studies and Phase‐1 safety studies without any adverse findings 6, 9…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Toxicity studies with PAP‐1 and the peptidic K V 1.3 blocker ShK‐186 have so far not revealed any toxicity despite 6 months or 28 days of continuous administration in rats or rhesus macaques 4, 8. PAP‐1 has further completed IND‐enabling toxicity studies, while ShK‐186 has passed both IND toxicity studies and Phase‐1 safety studies without any adverse findings 6, 9…”
Section: Discussionmentioning
confidence: 99%
“…4,8 PAP-1 has further completed INDenabling toxicity studies, while ShK-186 has passed both IND toxicity studies and Phase-1 safety studies without any adverse findings. 6,9 In conclusion, we are proposing Kv1.3 inhibitors as novel potential therapeutics for reducing secondary inflammatory damage in ischemic stroke by preferentially targeting "M1-like" microglia functions. Following this first pharmacological proof-of-concept study, PAP-1 and other small molecule Kv1.3 blockers should be further explored in alternative stroke models, that for example establish reperfusion with alteplase to increase translatability to human stroke, and also be studied in females and animals with comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dalazatide peptide recently underwent clinical trials in psoriasis and the patients showed an improvement of this condition. The clinical trial data has now been published (Tarcha et al, 2017)…”
Section: Sea Anemone Toxin and Immune Modulationmentioning
confidence: 99%
“…For example, the ShK peptide from the venom of sea anemone inhibits the Kv1.3 ion channel in T effector memory (TEM) cells, producing decreased cell proliferation and suppression of IL-2 production ( Beeton et al, 2005) . Furthermore, a derivative of ShK (dalazatide) recently completed a successful Phase I clinical trial in psoriasis patients (Tarcha et al, 2017) The systematic study of the venom components and their interaction with the immune system may reveal novel therapeutics for a plethora of human diseases and therapeutics against envenomation symptoms. Venoms are engaged by the immune system and a response is generated to counterbalance their effects.…”
Section: Introductionmentioning
confidence: 99%